A real-world, multi-site, observational study of infusion time and treatment satisfaction with rheumatoid arthritis patients treated with intravenous golimumab or infliximab. (3rd July 2018) - Daniel, Shoshana R.; McDermott, John D.; Le, Cathy; Pierce, Christine A.; Ziskind, Michael A.; Ellis, Lorie A.
Abstract: Objectives: To assess real-world infusion times for golimumab (GLM-IV) and infliximab (IFX) for rheumatoid arthritis (RA) patients and factors associated with treatment satisfaction. Methods: An observational study assessed infusion time including: clinic visit duration, RA medication preparation and infusion time, and infusion process time. Satisfaction was assessed by a modified Treatment Satisfaction Questionnaire for Medication (patient) and study-specific questionnaires (patient and clinic personnel). Comparative statistical testing for patient data utilized analysis of variance for continuous measures, and Fisher's exact or Chi-square test for categorical measures. Multivariate analysis was performed for the primary time endpoints and patient satisfaction. Results: One hundred and fifty patients were enrolled from six US sites (72 GLM-IV, 78 IFX). The majority of patients were female (80.0%) and Caucasian (88.7%). GLM-IV required fewer vials per infusion (3.7) compared to IFX (4.9; p  = .0001). Clinic visit duration (minutes) was shorter for GLM-IV (65.1) compared to IFX (153.1; p  < .0001), as was total infusion time for RA medication (32.8 GLM-IV, 119.5 IFX; p  < .0001) and infusion process times (45.8 GLM-IV, 134.1 IFX; p  < .0001). Patients treated with GLM-IV reported higher satisfaction ratings with infusion time ( p  < .0001) and total visit time ( p  = .0003). Clinic personnel reported higher satisfaction with GLM-IV than IFX specific to medication preparation time, ease of mixing RA medication, frequency of patients requiring pre-medication, and infusion time. Limitations: Findings may not be representative of care delivery for all RA infusion practices or RA patients. Conclusions: Shorter overall clinic visit duration, infusion process, and RA medication infusion times were observed for GLM-IV compared to IFX. A shorter duration in infusion time was associated with higher patient and clinic personnel satisfaction ratings.